Brain microvascular pathology in Susac syndrome: an electron microscopic study of five cases. (2nd November 2019) - Agamanolis, Dimitri P.; Prayson, Richard A.; Asdaghi, Negar; Gultekin, Sakir H.; Bigley, Kim; Rennebohm, Robert M.
ABSTRACT: Susac syndrome is a rare, immune-mediated disease characterized by encephalopathy, branch retinal artery occlusion, and hearing loss. Herein, we describe the electron microscopic findings of three brain biopsies and two brain autopsies performed on five patients whose working clinical diagnosis was Susac syndrome. In all five cases, the key findings were basement membrane thickening and collagen deposition in the perivascular space involving small vessels and leading to thickening of vessel walls, narrowing, and vascular occlusion. These findings indicate that Susac syndrome is a microvascular disease. Mononuclear cells were present in the perivascular space, underlining the inflammatory nature of the pathology. Though nonspecific, the changes can be distinguished from genetic and acquired small vessel diseases. The encephalopathy of Susac syndrome overlaps clinically with degenerative and infectious conditions, and brain biopsy may be used for its diagnosis. Its vascular etiology may not be obvious on light microscopy, and electron microscopy is important for its confirmation.